Multi-wavelength fabry-perot brillouin-erbium fibre laser - Al-Mansoori, M.H.; Adikan, Faisal Rafiq Mahamd; Naji, A.W.; Abdullah, M.K.; Mahdi, M.A. (2006)
Multi-wavelength Brillouin-Erbium fibre laser utilising fibre Fabry-Perot resonator is presented here. The proposed laser cavity used only a 980 nm laser diode and a coil of Erbium-doped fibre to produce cascaded Brillouin Stokes. The highest number of Stokes up to 43 lines with a spacing of 0.088 nm was obtained experimentally. (c) 2005 Elsevier GmbH. All rights reserved.